Experimental evidence of symmetry breaking of transition-path times - J. Gladrow (Nature Portfolio, 2019)
Microscopic transition mechanisms impact many biophysical systems. In this work, the authors explore transition path times between thermodynamic states experimentally, and show symmetry breaking in the transition times under an external force that drives the system out of equilibrium.